Association between social-cognitive factors and sexual intention towards pre-marital sex activity among school-going late adolescents in Kuantan, Pahang - Abdullah, Fa’iza; Zainuddin, Nur Akmanidar; Draman, Samsul; A. Rahman, Nor Azlina (2019)
The Theory of Planned Behavior (TPB) is determined by four main domains of social-cognitive factors; attitudes, social-norms, self-efficacy and sexual intention. This study aim to identify the socio-demographic and socio-cognitive factors associated with sexual intention towards premarital sex among schoolgoing late adolescent. Materials and method: Cross-sectional study was conducted in nine government secondary schools in Kuantan district between January-July 2018. A total of 466 self-administered validated Youth Sexual Intention Questionnaires(YSI-Q) data are collected among unmarried students aged 18-19year-old. Statistical analyses were done using IBM SPSS version 22.0. Results: Out of 466 participants, 67.4%, 68.2%, 64.4% are Malays, Females and Muslims. Simple logistic regression showed for every one unit increase in permissive attitude, socialnorms and self-efficacy scores, there were 1.424, 1.303 and 1.215 times increase risk of having sexual intention, with p -value of 0.001 each and 95% CI of odds ratio(OR) 1.268-1.600, 1.191-1.425 and 1.066-1.386 respectively. Multivariate logistic regression showed that female had lower risk of having sexual intention( p =0.001, OR=0.163, CI=0.058-0.462). Non-Malays and ever-smoker students had higher risk compared to Malay and non-smoker towards having sexual intention with p =0.001 (OR=5.110,CI=1.881-13.886) and p =0.019 (OR=3.288, CI=1.218-8.875) respectively. For every unit increase in permissive attitude score, there was 1.236 times increase risk of having sexual intention with p=0.002 (95%CI, OR=1.084-1.410). Conclusion: The study showed the risk of having sexual intention was higher among males, non-Malay, ever-smoker students; and those with higher permissive attitude scores. Peer education intervention programs are necessity for school-going students to improve the permissive attitude in averting risk behavior that may lead to sexual intention towards pre-marital sex activity. The study should be expanded to adolescent who are no longer in school or in suburban areas.